2021
DOI: 10.1371/journal.ppat.1009033
|View full text |Cite
|
Sign up to set email alerts
|

Novel modulators of p53-signaling encoded by unknown genes of emerging viruses

Abstract: The p53 transcription factor plays a key role both in cancer and in the cell-intrinsic response to infections. The ORFEOME project hypothesized that novel p53-virus interactions reside in hitherto uncharacterized, unknown, or hypothetical open reading frames (orfs) of human viruses. Hence, 172 orfs of unknown function from the emerging viruses SARS-Coronavirus, MERS-Coronavirus, influenza, Ebola, Zika (ZIKV), Chikungunya and Kaposi Sarcoma-associated herpesvirus (KSHV) were de novo synthesized, validated and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 90 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…Concerning the risk in interacting with the nuclear microenvironment (host DNA), it seems to be very low. In contrast, a recently published study reported the possibility for RNA viruses-including SARS-CoV-2-to interfere with the crucial p53 "guardian of the genome" nuclear phospoprotein function (Alzhanova et al, 2021). The precise period of time after vaccination characterized by high immunogenicity and the probability of vaccinated people to be able as carriers to spread the virus still remain unknown.…”
Section: Discussionmentioning
confidence: 97%
“…Concerning the risk in interacting with the nuclear microenvironment (host DNA), it seems to be very low. In contrast, a recently published study reported the possibility for RNA viruses-including SARS-CoV-2-to interfere with the crucial p53 "guardian of the genome" nuclear phospoprotein function (Alzhanova et al, 2021). The precise period of time after vaccination characterized by high immunogenicity and the probability of vaccinated people to be able as carriers to spread the virus still remain unknown.…”
Section: Discussionmentioning
confidence: 97%
“…Virtually, all viruses target molecular cellular mechanisms that can control their replication, dissemination, or persistence. Among these is p53, a key gatekeeper for cell division and survival that also regulates innate immune responses ( Alzhanova et al, 2021 ). The expression and activity of key transcriptional factors, such as p53 and NF-kB are altered upon SARS-CoV-2 infection, as well as other key molecules such as the virus host cell entry mediator ACE2, member of the renin-angiotensin system RAS-pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide sequences of ZIKV ORFs used in this study were derived from ZIKV strain H/PF/2013 (NCBI gene identifier number AHZ13508). The Heise lab (University of North Carolina, Chapel Hill, North Carolina, USA) provided their pOME plasmid-based library that permits expression of each ZIKV ORF containing a C-terminal 3XFLAG tag (35). To enable streptavidin-based affinity purification of ZIKV proteins, the ZIKV C, E, M, NS1, NS2B, and NS4A ORFs encoded in the pOME plasmids were subcloned into our modified pCAGGS expression vector (36, 37) such that they would encode a C-terminal streptavidin binding peptide (SBP) (MDEKTTGWRGGHVVEGLAGELEQLRARLEHHPQGQREP) in place of the 3XFLAG tag.…”
Section: Methodsmentioning
confidence: 99%